2021
DOI: 10.1177/1178632921999652
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Implementation Science in Advancing Resource Generation for Health Interventions in Low- and Middle-Income Countries

Abstract: Low- and middle-income countries (LMICs) bear the brunt of communicable and non-communicable diseases and experience higher mortality and poor health outcomes compared to resource-rich countries. Chronic resource deficits in LMICs impede their ability to successfully address vexing health issues. Implementation science provides researchers with an approach to develop specific interventions that can generate and/or maximize resources to facilitate the implementation of other public health interventions, in reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Correct use of any evidence-based practice is integral to assuring impact, and quality of use must be measured and iteratively improved over time. Process evaluation is a strategy to identify and address gaps at each level of an intervention to maximize implementation success and address barriers to successful use ( 19 , 20 ). Understanding how PEWS impacts are interrelated helps explain how they are achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Correct use of any evidence-based practice is integral to assuring impact, and quality of use must be measured and iteratively improved over time. Process evaluation is a strategy to identify and address gaps at each level of an intervention to maximize implementation success and address barriers to successful use ( 19 , 20 ). Understanding how PEWS impacts are interrelated helps explain how they are achieved.…”
Section: Discussionmentioning
confidence: 99%
“…When evidence discourse includes experience, researchers seem to present it as the need to understand the power dynamics of policymaking, politicians' needs, and the political landscape. Some implementation researchers note that to ensure the adoption of evidence-based policies, researchers and implementers must intentionally incorporate elements for successful implementation into the planning and formulation of policies (Bullock et al, 2021;Ojo et al, 2021;Proctor et al, 2011).…”
Section: Understanding Evidence-based Policymakingmentioning
confidence: 99%
“…This determinant framework incorporates contextual and determinant factors influencing the success or failure of policy implementations. Although other existing frameworks might adequately reveal and explain contextual issues, the CFIR appears to be the most common among LMICs (Means et al, 2020;Ojo et al, 2021). There are five CFIR domains: Intervention Characteristics, Characteristics of Individuals, Outer Setting, Inner Setting, and Process.…”
Section: Applying Consolidated Framework For Implementation Research ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lessons from the treatment of HIV have demonstrated that even complex and expensive treatments are possible when accompanied by innovative treatment models and new investments [ 12 ]. Therefore, facilitating the successful adoption of medications like blinatumomab in LMICs requires an approach that addresses cost but also an implementation approach to maximize existing resources and address therapeutic challenges and barriers related to organizational context [ 19 ]. Currently, there is no implementation framework for novel pediatric cancer interventions in a global setting.…”
Section: Introductionmentioning
confidence: 99%